Stress and health education actions: promotion context of mental health at work - Souza, Adriano Rodrigues de; Moraes, Leila Memória Paiva; Barros, Maria Grasiela Teixeira; Vieira, Neiva Francenely Cunha; Braga, Violante Augusta Batista (Rev Rene, 2007)
This is a bibliographical study which has as objective to analyze, critically the scientific productions indexed in the Lilacs that are about health education actions in mental health promotion, with emphasis on the relation between stress and work. It was identified a reduced number of productions on the worker’s health essentially, what indicates the existence of a theoretical gap which can be an indication of a little consistent or inexistent practice in many cases. We point to the urgency of bringing this problem out, calling the attention of professionals and managers for the necessity of observing and attending this increasing requirement of population .